The Impact of Self-Agitating Anaerobic Batch Digester Design on Biogas Production of Cattle Manure Co-Digested with Lemna minor - Navarro, Aj S. (Animo Repository, 2022)
The continuation of utilizing fossil fuels as cooking energy sources in rural communities in the Philippines causes more citizens to be at risk of developing numerous health illnesses. This study aimed to propose a potential solution to this problem by innovating a self-agitating anaerobic batch digester, promoting biogas production of cattle manure co-digested with Lemna minor. Two anaerobic batch digester designs, one with baffles and one without, were observed within 22 days to determine the impact of the anaerobic digester design on mixing and biogas production yield. The study contained two pairs of anaerobic batch digesters, the initial and improved digester. The water displacement method was used to measure the biogas yield from the initial and improved digesters. The results of this study on the quantity of biogas produced between the initial experimental designs measured every six days and revised experimental designs measured every four days concluded that anaerobic batch digester designs with baffles produced a superior amount of biogas with 5468.88 cm³ more yield than the digester without baffles. Utilizing an Independent Sample T-test, the difference in biogas production is considered significant, (p = .174). Similar studies in the future are encouraged to explore variations in the anaerobic digester design outside of the placement of baffles, including factors such as the materials used and the period of observation due to the limitations of this study.